Eating behaviour and nutritional knowledge in elite adolescents practising synchronised swimming. A nutritional intervention - Ghiani, G.; Magnani, S.; Di Giacomo, A.; Vanni, S.; Sainas, G.; Palazzolo, G.; Ruiu, P.; Crisafulli, A.; Tocco, F. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Synchronized swimming combines speed, power and endurance with precise synchronized movements and high-risk acrobatic manoeuvres. Because of the aesthetic nature of the sport, which prioritizes leanness, the risks of energy and macronutrient deficiencies are a significant concern. Relative Energy Deficiency in Sport (RDA-s) and disordered eating/eating disorders are also of concern for these female athletes (Robertson et al., 2014). The aim of this study was to check whether a group of elite adolescent practising synchronised swimming had a proper diet matching the Italian nutritional advices, and to program a nutritional intervention for the athletes and their families and coaches. Methods: 13 elite adolescents synchronized swimmers (age 15±1.0 years, BMI 21±2.4, fat mass 26.7 ±8.4%) participated in the study. They attended an interview about their life style and their training and a validated dietary questionnaire on food habits, eating behaviour and nutritional knowledge of adolescents (Turconi et al., 2003). Then data were compared with the nutritional advices from the Italian Government and some nutritional interventions were made to help the athletes to reach a better nutritional status. For each subject fat mass was detected by means of plicometry method (Slaughter et al., 1988). Results: The processing of the questionnaire evidenced a lack in the consumption of carbohydrates, fruits and vegetables. Moreover, 17% of the athletes had the habit of totally skipping breakfast and all of them reported inadequate daily distribution of meals. Finally, questionnaire highlighted serious problems with the lunch management because their daily training in the swimming pool was too close to lunchtime. Discussion: Disordered eating behaviour and eating disorders are of great concern because of their associations with physical and mental health risks and, in the case of athletes, impaired performance. To prevent RDA-s, aquatic athletes have to practice healthy eating behaviour, and coaches and athletes` health care teams must be conscious that early interventions are needed to prevent this kind of problems especially in adolescents athletes (Melin et al., 2014).